’’Wirtualizacja’’ urzędów samorządowych w Polsce - Stachowiak, Zbigniew (Gospodarka w Praktyce i Teorii, 2012)
The purpose of this article is to find out if a local government in Poland can work virtually. The author of this article made a review of a local government structure and tasks and e-government projects in Poland. He also made some remarks about Business Continuity Plans in it.